2021
DOI: 10.3390/ani11123384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementary Levels of Rumen-Protected Lysine and Methionine on Growth Performance, Carcass Traits, and Meat Quality in Feedlot Yaks (Bos grunniens)

Abstract: Yak, a unique bovine species on the Qinghai-Tibetan Plateau, has provided pastoralists with the basic materials of production and life for thousands of years. Existing literature showed that yak meat is of high nutritional value for humans whereas the growth performance is relatively low. As it has been demonstrated, lysine and methionine are the two key limiting amino acids in ruminants. Therefore, this study was conducted to investigate the effect of supplementary levels of rumen-protected lysine (RPL) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…4 Protein-protein interaction (PPI) network. Red represents the core genes, Blue represents differentially expressed genes Met supplementation in feedlot Yaks [17]. In the present study, the final body weight with Lys/Met at ratio 1:1 was increased of Tibetan sheep.…”
Section: Discussionsupporting
confidence: 47%
“…4 Protein-protein interaction (PPI) network. Red represents the core genes, Blue represents differentially expressed genes Met supplementation in feedlot Yaks [17]. In the present study, the final body weight with Lys/Met at ratio 1:1 was increased of Tibetan sheep.…”
Section: Discussionsupporting
confidence: 47%
“…The increased metabolizable Lys balance may have impacted performance if other AAs were imbalanced. Ma et al (2021) observed differences in the ADG and feed-to-gain ratio in yaks in a feedlot with four supplementary levels of RP-Lys and Met in the diets. They concluded that growth performance and meat quality could be improved by supplementing RP-AAs in the diets.…”
Section: Discussionmentioning
confidence: 82%
“…Heiderscheit and Hansen (2020) reported no differences in the carcass characteristics of Angus crossbred steers fed supplemental RP-Lys diets. Similarly, Ma et al (2021), in their study with different levels of protected Lys and Met, found no differences in carcass characteristics. In diets with varying levels of CP and Lys-to-Met ratios, Prado et al (2014) did not observe significant differences in carcass conformation and fatness score.…”
Section: Discussionmentioning
confidence: 86%
“…In their study of meat tenderness, Haiqing et al found that adding different concentrations of RPMET to the diet of Tan sheep did not significantly affect the SF ( Li et al, 2020 ). In fact, the study by Zhiyuan et al showed that low to medium concentrations of RPLYS and RPMET significantly reduced the SF of yak meat ( Ma et al, 2021 ). On the other hand, in this study, the addition of RPSAA was found to significantly increase the SF of Tibetan sheep meat.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, RPAA can reduce the degradation within the rumen, thereby allowing the amino acids to enter the small intestine. This not only improves the utilization rate of amino acids but also increases animal production ( Ma et al, 2021 ; Liu et al, 2023 ). However, RPAA decomposed in the rumen and entering the small intestine may also alter the gastrointestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%